PENGARUH CAR, FDR, NPF, DAN BOPO TERHADAP PROFITABILITAS (RETURN ON EQUITY) (Studi Empiris pada Bank Umum Syariah di Indonesia Periode Tahun 2009-2013) - Aulia, Farrashita; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2016)
The objectives of this research is to analyze the influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), and Operational Efficiency Ratio (BOPO) to Return On Equity (ROE) as a proxy of Islamic’s Bank profitability in Indonesia during 2009-2013 periods. Sample population of this research are ten Islamic’s Banks selected using purposive sampling technique. The analysis technique is using multiple regression. This research uses secondary data from The Islamic Bank’s annual published financial reports during 2009-2013 periods. Meanwhile, the classical assumptions test used in this study are autocorrelation, normality, multicollinearity, and heteroscedasticity. The result of this research shows that CAR and BOPO had a negative and significantly influence on ROE. FDR had a negative influence on ROE, but it doesn’t significantly influence ROE. meanwhile, NPF has a positive and significant influence on ROE.